Do Childhood Cancer Survivors Meet the Diet and Physical Activity Guidelines? A Review of Guidelines and Literature - Zhang, Fang Fang; Saltzman, Edward; Must, Aviva; Parsons, Susan K. (International Journal of Child Health and Nutrition, 2012)
Despite advances in cancer treatment, childhood cancer survivors are at higher risk of developing chronic health conditions than peers who have not had cancer. Being overweight or obese adds to the already elevated risk of cardiovascular diseases and metabolic abnormalities. Diet and physical activity are modifiable behaviors that reduce obesity risk and have been shown to improve cancer survival in adult cancer survivors. Specific guidelines have been developed for cancer survivors that provide advice on nutrition, physical activity and weight management following cancer diagnosis and treatment. In this review, we report on existing nutrition and physical activity guidelines for cancer survivors, supplemented by available literature on diet and physical activity status of childhood cancer survivors and their associations with health-related outcomes. The 2012 American Cancer Society (ACS) and the 2008 Children’s Oncology Group (COG) guidelines provide similar advice on diet but the ACS guidelines also offer specific advice on physical activity and weight management. Thirty-one observational studies and 18 intervention trials published prior to June 2012 that met the inclusion criteria were reviewed. Results suggest that a high proportion of childhood cancer survivors had poor adherence to dietary and physical activity guidelines. Although findings from existing intervention trials are preliminary due to small sample size, available evidence suggests that exercise intervention is safe and feasible for patients and survivors of childhood cancer. Childhood cancer survivors should be encouraged to engage in physical activity, adopt a healthy diet, and maintain a healthy weight throughout cancer survivorship.